Employment, income and the mobilistion of local resources in three thai village (Bangkok, 1982)
Based on a survey of three villages in three regions of Thailand, the present study examines the patterns of employment, production, distribution of income and assets, and land tenure and explores the possibility of expand ing employment and income through the mobilisation of local resources at the village level. The expansion of productive employment is the central concern of this work. The study includes an estimate of the employment potential and discusses the obstacles to its realisation.
Keywords: Income